Two Types of Management for the Noninvasive Treatment of Pectus Excavatum in Neonatal Puppies—Case Reports - Pereira, Keylla Helena Nobre Pacífico [UNESP]; Fuchs, Kárita da Mata [UNESP]; Terçariol, Lara Ataídes Arantes; Silva, Renata Cesar [UNESP]; Camargo, Gabriel de Azevedo [UNESP]; Mendonça, Júlia Cosenza [UNESP]; Paulino, Netelin Tainara; Zone, Marcelo Alejandro; Oba, Eunice [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (MDPI, 2023)
Pectus excavatum is a deformity of the thorax characterized by ventrodorsal narrowing of the sternum bone and costal cartilages, which can lead to compression and cardiopulmonary alterations in dogs, presenting a high prevalence in brachycephalic breeds. The aim of this report was to describe two types of management for the noninvasive treatment of pectus excavatum in newborn puppies of the breeds French Bulldog and American Bully. The puppies presented dyspnea, cyanosis and substernal retraction during inspiration. The diagnosis was performed by physical examination and confirmed by chest X-ray. Two types of splints were performed (a circular splint with plastic pipe and a paper box splint on the chest), aiming at thoracic lateral compression and frontal chest remodeling. The management was effective for the conservative treatment of mild-grade pectus excavatum, resulting in the repositioning of the thorax and improvement of the respiratory pattern.
Keywords: bandage; brachycephalic breeds; congenital malformation; dog; dyspnea; splint; thorax